Urban stormwater management under various runoff conditions for Arba Minch town of southern Ethiopia - Bereket Ayele Ayda; Demelash Wondimagegnehu Goshime; Mekuanent Muluneh Finsa; Abebe Temesgen Ayalew (Natural Hazards Research)
Ineffective urban stormwater management causes increased surface runoff, and impacts on infrastructure and human life. However, urban stormwater condition is not quantified in Arba Minch area, which cause significant damage on the infrastructures as residence and roads. Therefore, the main objective of this study is to evaluate the condition of urban stormwater under different runoff conditions using Stormwater Management Model (SWMM) in Arba Minch town, specifically Sekela sub city. A combination of field, satellite, observed and laboratory test-based data on drainage systems, infiltration and % imperviousness was collected. The catchment is divided into 47 sub-catchments depend on the building block, flow direction, and drainage networks. The sub-catchments with the average surface runoff revealed 0.07 ​m3/s, 0.14 ​m3/s, 0.25 ​m3/s, 0.65 ​m3/s, and 0.75 ​m3/s over a 2-year, 5-year, 10-year, 25-year, and 30-year return period, respectively. The maximum nodes flooded occur at junctions’ number (J7, J8, J24, and J25), as well as conduits (C14, C18, and C27), according to simulation findings of 2-year return period design rainfall which align with the major cause area. For return periods of 2, 5, 10, 25, and 30 years, the peak runoff result was greatest in sub-catchments SC-1, SC-6, SC-8, SC-9, and SC-30. This depicts sub-catchments in the area are flooded, hence resizing of canals and other drainage structures are necessary to mitigate the stormwater. The SWMM simulated results for 2-year, 5-year, 10-year, 25-year, and 30-year return periods showed peak runoff was greatest in sub-catchments No.8, 1, 6, 30, and 9 because of the slope of the sub-catchment and their large area with high percent imperviousness that results in less infiltration into the soil. The finding of this study shows a rapid increase in surface runoff, which mainly related to impermeable surface and inadequate urban drainage systems leading to damage to infrastructures and properties. This study suggests, a mitigation measures should be adopted to minimize the effect of stormwater using stormwater various intervention approaches following multi program combined with various runoff condition which is very important for road protection authorities, decision makers, and the scientific community to support future water related researches.